2019
DOI: 10.1016/j.sjbs.2018.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial potential of some Saudi honeys from Asir region against selected pathogenic bacteria

Abstract: Honey is a nutrient rich natural product and has been utilized as traditional and complementary medicine since ancient times. In this study, antibacterial activity of Sider (Ziziphus spina-christi), Dharm (Lavandula dentata), and Majra (Hypoestes forskaolii) honey samples collected from Asir region of Saudi Arabia was in vitro evaluated at 80% and 50% w/v concentrations against five pathogenic bacteria i.e. Escherichia coli, Proteus mirabilis, Staphylococcus aureus, Shigella flexneri, and Staphylococcus epider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 34 publications
2
22
0
4
Order By: Relevance
“…The antibacterial activity of honey is strictly related to botanical source, the metabolism of honey bees, environmental-seasonal-climatic processing procedures and storage conditions, which have a strong influence on the physical and chemical property of this “medical” food, including antimicrobial properties [ 14 , 15 , 16 , 17 , 26 , 27 , 28 , 29 , 30 ]. Antimicrobial compounds of honey can be divided in two different groups: those with peroxide action and those with non-peroxide action.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibacterial activity of honey is strictly related to botanical source, the metabolism of honey bees, environmental-seasonal-climatic processing procedures and storage conditions, which have a strong influence on the physical and chemical property of this “medical” food, including antimicrobial properties [ 14 , 15 , 16 , 17 , 26 , 27 , 28 , 29 , 30 ]. Antimicrobial compounds of honey can be divided in two different groups: those with peroxide action and those with non-peroxide action.…”
Section: Discussionmentioning
confidence: 99%
“…Honey antibacterial activity against S. aureus , E. coli , and Salmonella sp. could vary on the basis of two honey sample features: floral origin diversity and countries of origin [ 14 , 15 , 16 , 17 , 18 , 19 ]. It has been shown that honeys with low levels of phenol and tocopherol have the highest antibacterial activity against clinical isolates of S. aureus, Proteus mirabilis , E. coli , and Shigella dysenteriae [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of floral origin and altitude on physiochemical properties and concentration of vitamins was analyzed by Al-Mosa et al, 2019 , Mohammed et al, 2019 . Many researchers worked on antimicrobial ( Abdallah and Hamed, 2019 , Al-Hindi and Shehata, 2014 , Ansari et al, 2017a , Ghramh et al, 2019a , Ghramh et al, 2019b , Owayss et al, 2019 ), antioxidant ( Al-Hindi and Shehata, 2014 ), physicochemical properties including some quality parameters ( Ahamed et al, 2017 , Alqarni et al, 2014 , Alqarni et al, 2016 , Mesallam and El-Shaarawy, 1987 , Osman et al, 2007 ), mineral contents ( Al-Hindi and Shehata, 2014 , Alqarni et al, 2014 , Arida et al, 2012 , Osman et al, 2007 , Taha et al, 2018 ), floral pigments ( Alqarni et al, 2016 ), heavy metals ( Bazeyad et al, 2019 ), validation of botanical origins and geographical sources through ultraviolet spectroscopy and chemo metric analysis ( Ansari et al, 2018 ), and formation and biological activities of nanoparticles by using honey samples ( Al-Brahim and Mohammed, 2020 , Ghramh et al, 2019b ). Most of the previous research on honey deals with the above-mentioned parameters rather than quantifying the two most important quality parameters (sucrose and HMF) present in honey samples.…”
Section: Introductionmentioning
confidence: 99%
“…Another plausibility is the structure of honey, which has in excess of 181 constituents (Mandal & Mandal, 2011;Vallianou et al, 2014). Hydrogen peroxide and phenolic components are the significant supporters of the antimicrobial action of honey, and the difference in quantities of these components in various honey bring about their ability as antimicrobial agents (Almasaudi et al, 2017 (Beno-Costa et al, 2016;Wasihun & Kasa, 2016;Deng et al, 2018;Ghramh et al, 2019). Over and aimless utilization of antibiotics agents has prompted the rise of multidrug-resistant bacterial strains, a worldwide general medical issue (Kacaniova et al 2011;Wasihun & Kasa, 2016).…”
Section: Introductionmentioning
confidence: 99%